MEMBUAT CATATAN BAGI PEMBICARA, SLIDE SHOW DAN PENCETAKAN - Crisita Revani Takalawesang; Britania Bawuntu; Cornelia Angie Palilingan; Elisabeth Limbong; Mutiara Lauma; Reisyella Tangkilisan; Salsabillah Putri Lamato; Stella Pogo; Naila Ninta Br Tarigan (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2024)
Speaker notes, lide shows, and printed materials are three key components of an effective presentation. Speaker notes help structure the flow and focus of the content, while slide shows serve as visual support to clarify and engage the audience. Printed materials provide additional information that the audience can access after the presentation. The combination of these three elements supports a structured, engaging, and memorable message delivery, enhancing communication effectiveness and information retention.